Internalisasi Nilai-Nilai Moderasi Beragama dalam Pembelajaran PAI di SMPIT Se-Kalimantan Tengah - Zulkarnain, Ali Iskandar; Azis, Abdul; Hamdi, Hamdi (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
This research departs from the phenomenon of radicalism and intolerance that occurs a lot among students such as fights, tauran and others which this condition raises deep concerns from all circles: academics, religionists, civil society, central and local governments. While facts in the field show that PAI learning is currently not optimal and is still unable to provide a good understanding to students, especially about the values of religious moderation. The purpose of this study is to describe the implementation of internalization of religious moderation values in Islamic Religious Education learning in SMPIT throughout Central Kalimantan. This study used descriptive qualitative methods with data collection techniques through observation, interviews, and documentation.The subjects in this study were Islamic Religious Education Teachers and students, and the Principal as informants. The data validation technique in this study used source triangulation. The data analysis technique uses data collection, data reduction, data presentation, and drawing conclusions. The results showed that: The implementation of internalization of religious moderation values in Islamic Religious Education learning at SMPIT throughout Central Kalimantan has been carried out well by Islamic Religious Education teachers, namely since planning, implementation and evaluation activities